Modern Use of Water Produced by Purification of Municipal Wastewater: A Case Study - Giorgia Tomassi; Pietro Romano; Gabriele Di Giacomo (Energies, 2021)
All the urban areas of developed countries have hydric distribution grids and sewage systems for collecting municipal wastewater to treatment plants. In this way, the municipal wastewater is purified from human excreta and other minor contaminants while producing excess sludges and purified water. In arid and semi-arid areas of the world, the purified water can be used, before discharging, to enhance the energy efficiency of seawater desalination and solve the problems of marine pollution created by desalination plants. Over the past half-century, seawater desalination has gradually met demand in urbanized, oil-rich, arid areas. At the same time, technological evolution has made it possible to significantly increase the energy efficiency of the plants and reduce the unit cost of the produced water. However, for some years, these trends have flattened out. The purified water passes through the hybridized desalination plant and produces renewable osmotic energy before the final discharge in the sea to restart the descent behaviour. Current technological development of reverse osmosis (RO), pressure retarded osmosis (PRO) and very efficient energy recovery devices (ERDs) allows this. Furthermore, it is reasonable to predict that, in the short-medium term, a new generation of membranes specifically designed for improving the performance of the pressure retarded osmosis will be available. In such circumstances, the presently estimated 13-20% decrease of the specific energy consumption will improve up to more than 30%. With the hybrid plant, the salinity of the final discharged brine is like that of seawater, while the adverse effect of GHG emission will be significantly mitigated.